Living with the user: design drama for dementia care through responsive scripted experiences in the home - Coughlan, Tim; Brown, Michael; Lawson, Glyn; McAuley, Derek; Baurley, Sharon; Tsai, Allen; Koppe, Therese; Elliott, Meretta; Green, Stephen; Martin, Jennifer L. (2014)
Participation in forms of drama and narrative can provoke empathy and creativity in user-centred design processes. In this paper, we expand upon existing methods to explore the potential for responsive scripted experiences that are delivered through the combination of sensors and output devices placed in a home. The approach is being developed in the context of Dementia care, where the capacity for rich user participation in design activities is limited. In this case, a system can act as a proxy for a person with Dementia, allowing designers to gain experiences and insight as to what it is like to provide care for, and live with, this person. We describe the rationale behind the approach, a prototype system architecture, and our current work to explore the creation of scripted experiences for design, played out though UbiComp technologies.